Optimising bismuth magnesium niobate pyrochlores as potential ceramic dielectrics: Reaction progression, phase equilibria and impedance properties - Tan, Kar Ban; Tan, P.Y.; Feng, Y.; Khaw, C.C.; Lim, T.Z. Alvin; Kechik, M.M.A.; Chen, S.K.; Chan, K.Y.; Lu, M.; Sun, J.; Zhou, D. (Elsevier, 2025)
The phase-pure Bi2O3-MgO-M2O5 (BMN) cubic pyrochlores formed across a broad compositional range, with bismuth content varying from 41.88 to 44.50 mol %. The quadrilateral subsolidus region is defined by two substitution mechanisms: (i) Mg2+ substitution by Nb5+, balanced by oxygen stoichiometry variations and (ii) one-to-one Bi3+ replacement by Nb5+, with charge compensation by O2− . This yields a general formula of Bi3.36+xMg1.92-yNb2.72-x + yO13.76-x+(3/2)y, involving two variables with the corresponding subsolidus solution limits of 0.10 ≤ x ≤ 0.20 and 0.00 ≤ y ≤ 0.16, respectively. Notably, these BMN pyrochlores exhibit high dielectric constants, ε′ in the range of 167–204 at 30 ◦C, 1 MHz and low dielectric losses, tan δ in the order of 10− 4 - 10− 3 . The elevated dielectric constant is likely due to the enhanced polarisability of Nb2O5 within the crucial BO6 octahedra of the pyrochlore structure. Furthermore, these pyrochlores display negative temperature coefficients of permittivity, TCε’ ranging from − 528 to − 742 ppm/◦C at 30–300 ◦C and 1 MHz. These thermally stable and highly insulating BMN pyrochlores with high activation energies, Ea >1.0 eV, are promising candidate for potential application in ceramic capacitors.